Neonatologists and neonatal nurses have positive attitudes towards perinatal end‐of‐life decisions, a nationwide survey. (12th April 2019) - Dombrecht, Laure; Deliens, Luc; Chambaere, Kenneth; Baes, Saskia; Cools, Filip; Goossens, Linde; Naulaers, Gunnar; Roets, Ellen; Piette, Veerle; Cohen, Joachim; Beernaert, Kim
Abstract: Aim: Perinatal death is often preceded by an end‐of‐life decision (ELD). Disparate hospital policies, complex legal frameworks and ethically difficult cases make attitudes important. This study investigated attitudes of neonatologists and nurses towards perinatal ELDs. Methods: A survey was handed out to all neonatologists and neonatal nurses in all eight neonatal intensive care units in Flanders, Belgium in May 2017. Respondents indicated agreement with statements regarding perinatal ELDs on a Likert‐scale and sent back questionnaires via mail. Results: The response rate was 49.5% (302/610). Most neonatologists and nurses found nontreatment decisions such as withholding or withdrawing treatment acceptable (90–100%). Termination of pregnancy when the foetus is viable in cases of severe or lethal foetal problems was considered highly acceptable in both groups (80–98%). Physicians and nurses do not find different ELDs equally acceptable, e.g. nurses more often than physicians (74% vs 60%, p = 0.017) agree that it is acceptable in certain cases to administer medication with the explicit intention of hastening death. Conclusion: There was considerable support for both prenatal and neonatal ELDs, even for decisions that currently fall outside the Belgian legal framework. Differences between neonatologists' and nurses' attitudes indicate that both opinions should be heard during ELD‐making. Abstract :